Embodied Medicine: Mens Sana in Corpore Virtuale Sano - Riva, Giuseppe; Serino, Silvia; Di Lernia, Daniele; Pavone, Enea Francesco; Dakanalis, Antonios (Frontiers in Human Neuroscience, 2017)
Progress in medical science and technology drastically improved physicians’ ability to interact with patient’s physical body. Nevertheless, medicine still addresses the human body from an Hippocratic point of view, considering the organism and its processes just as a matter of mechanics and fluids. However, the interaction between the cognitive neuroscience of bodily self-consciousness (BSC), fundamentally rooted in the integration of multisensory bodily inputs, with virtual reality (VR), haptic technologies and robotics is giving a new meaning to the classic Juvenal’s latin dictum “Mens sana in corpore sano” (a healthy mind in a healthy body). This vision provides the basis for a new research field, “Embodied Medicine”: the use of advanced technologies for altering the experience of being in a body with the goal of improving health and well-being. Up to now, most of the research efforts in the field have been focused upon how external bodily information is processed and integrated. Nonetheless, these approaches lacked to consider a peculiar feature of the human body, the multisensory integration of internal inputs (interoceptive, proprioceptive and vestibular) that constitute our inner body dimension. So, as outlined in this perspective article, a future challenge is to bridge VR with bio/neuro-feedback and brain/body stimulation technologies also able to measure and modulate this internal/inner experience of the body. Finally, we also proposed the concept of “Sonoception” as an extension of this approach. The core idea is to exploit recent technological advances in the acoustic field to use sound and vibrations to modify the internal/inner body experience.